KONSTRUKSI SOSIAL PERAN PEMUKA AGAMA DALAM MENCIPTAKAN KOHESIVITAS KOMUNIKASI SOSIAL DI KOTA MATARAM - Basuki Basuki; Isbandi Isbandi (Jurnal Ilmu Komunikasi, 2008)
Divergency of believing in God gets impact on existing of beliefs & Relegions. This bring a Conssequency of culture (Values, norms, behavior) among differnt believers. That divergency born some fritions or coflient between different community in interaction, the outstanding relegions people hold important role in creating cohesivity among different community. This reseach purpose to explore how the outstanding relegion people in two villages construct their role in creating social communication cohesivity between Hindus & moslems in Cakranegara village & Karang Taliwang Village in Mataram City.